Making the Most of Mess: Reliability and Policy in Today's Management Challenges - Roe, Emery (Duke University Press Books, 2013)
In Making the Most of Mess, Emery Roe emphasizes that policy messes ca nnot be avoided or cleaned up; they need to be managed. He shows how p olicymakers and other professionals can learn these necessary skills f rom control operators who manage large critical infrastructures such a s water supplies, telecommunications systems, and electricity grids. T he ways in which they prevent major accidents and failures offer model s for policymakers and other professionals to manage the messes they f ace.Throughout, Roe focuses on the global financial mess of 2008 and i ts ongoing aftermath, showing how mismanagement has allowed it to morp h into other national and international messes. More effective managem ent is still possible for this and many other policy messes but that r equires better recognition of patterns and formulation of scenarios, a s well as the ability to translate pattern and scenario into reliabili ty. Developing networks of professionals who respond to messes is part icularly important. Roe describes how these networks enable the avoida nce of bad or worse messes, take advantage of opportunities resulting from messes, and address societal and professional challenges. In addi tion to finance, he draws from a wide range of case material in other policy arenas. Roe demonstrates that knowing how to manage policy mess es is the best approach to preventing crises.